GC-MS ANALYSIS OF PETROLEUM ETHER AND METHANOL EXTRACTS OF SOLANUM VIRGINIANUM L LEAVES - S. SUNDAR; Y. JUSTIN KOIL PILLAI (International Journal of Pharma and Bio Sciences, 2014)
The aim of the study was to investigate the phytoconstituents present in petroleum ether and methanolic extract of Solanum virginianum L leaves by Gas Chromatography & Mass Spectroscopic method. In the GC-MS analysis, five phytochemical components were identified in the petroleum ether extract and seven phytochemical components were identified in the methanolic extract of Solanum virginianum L. GC-MS analysis of Solanum virginianum L petroleum ether extract revealed the existence of the major compounds such as Aspidospermidin-17-ol,1-acetyl-19,21-epoxy-15,16-dimethoxy (Retention time11.58), L-(+)-Ascorbic acid 2, 6-dihexadecanoate (Retention time15.38), Estra-1,3,5 (10)-trien-17-ol (Retention time18.77) and the chemical constituents were identified in methanolic extract are N,N’Dibenzylidene-3,3’-dichlorobenzidine (Retention time 9.42),16-Allopregnen,3a,7a,11a-triol-20-one, triacetate (Retention time14.27). This type of GC-MS analysis is the first step towards understanding the nature of active principles in this plant.